The Management Internship - Gore, George J. (Academy of Management Journal, 1968)
This article levels a finger at the lack of uniform practice requirements in management education. The author questions the current practice whereby a large percentage of new Ph.D.'s and DBA's enter the field without having had any prior direct and meaningful contact with the business world.